2016
DOI: 10.2142/biophysico.13.0_281
|View full text |Cite
|
Sign up to set email alerts
|

Cooperativity and modularity in protein folding

Abstract: A simple statistical mechanical model proposed by Wako and Saitô has explained the aspects of protein folding surprisingly well. This model was systematically applied to multiple proteins by Muñoz and Eaton and has since been referred to as the Wako-Saitô-Muñoz-Eaton (WSME) model. The success of the WSME model in explaining the folding of many proteins has verified the hypothesis that the folding is dominated by native interactions, which makes the energy landscape globally biased toward native conformation. U… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 74 publications
(133 reference statements)
0
9
0
Order By: Relevance
“…Consequently, the WSME model guarantees that both the principle of minimal frustration and consistency principle that locally stable structure is consistent with the final folded, globally stable structure (Gō 1983 ; Bryngelson et al 1995 ). Previous studies showed that the WSME model accurately explains the experimentally observed folding mechanism, i.e., the nucleation–condensation mechanism, of small single-domain proteins (Muñoz and Eaton 1999 ; Itoh and Sasai 2006 ; Sasai et al 2016 ). These results suggest that real small proteins behave as ideal foldable proteins and that the consistency principle holds for small proteins.…”
Section: Folding Mechanisms Of Globular Proteinsmentioning
confidence: 85%
See 2 more Smart Citations
“…Consequently, the WSME model guarantees that both the principle of minimal frustration and consistency principle that locally stable structure is consistent with the final folded, globally stable structure (Gō 1983 ; Bryngelson et al 1995 ). Previous studies showed that the WSME model accurately explains the experimentally observed folding mechanism, i.e., the nucleation–condensation mechanism, of small single-domain proteins (Muñoz and Eaton 1999 ; Itoh and Sasai 2006 ; Sasai et al 2016 ). These results suggest that real small proteins behave as ideal foldable proteins and that the consistency principle holds for small proteins.…”
Section: Folding Mechanisms Of Globular Proteinsmentioning
confidence: 85%
“…Development of theoretical methods for predicting a folding energy landscape and native structure using only an amino acid sequence is one of the major goals of theoretical studies of protein folding (Dill et al 2008 ). One of the most promising theoretical models describing protein folding mechanisms is the Wako–Saitô–Muñoz–Eaton (WSME) model (or island model) (Wako and Saitô 1978a , b ; Muñoz and Eaton 1999 ; Sasai et al 2016 ). The WSME model is a coarse-grained, statistical mechanical model of proteins and enables one to draw a free-energy landscape of a protein-folding reaction using information from the native structure.…”
Section: Folding Mechanisms Of Globular Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Wako-Saitô-Muñoz-Eaton (WSME) model is one such statistical mechanical model that was first developed by Wako and Saitô ( Wako and Saito, 1978a , Wako and Saito, 1978b ), discussed in detail by Gō and Abe ( Go and Abe, 1981 , Abe and Go, 1981 ), and then later independently developed by Muñoz and Eaton (1999) . Originally seen as a physical tool to predict the folding rates of proteins from three-dimensional structures ( Muñoz and Eaton, 1999 , Henry and Eaton, 2004 ), the model has expanded its scope to quantitatively analyze folding behaviors of folded globular domains ( Bruscolini and Naganathan, 2011 , Garcia-Mira et al., 2002 , Narayan and Naganathan, 2014 , Narayan and Naganathan, 2017 , Narayan and Naganathan, 2018 , Naganathan and Muñoz, 2014 , Naganathan et al., 2015 , Munshi and Naganathan, 2015 , Rajasekaran et al., 2016 , Narayan et al., 2017 , Itoh and Sasai, 2006 ), repeat proteins ( Faccin et al., 2011 , Sivanandan and Naganathan, 2013 , Hutton et al., 2015 ), disordered proteins (with appropriate controls) ( Naganathan and Orozco, 2013 , Gopi et al., 2015 , Munshi et al., 2018a ), predict and engineer thermodynamic stabilities of proteins via mutations ( Naganathan, 2012 , Naganathan, 2013b , Rajasekaran et al., 2017 ) and entropic effects ( Rajasekaran et al., 2016 ), model allosteric transitions ( Itoh and Sasai, 2011 , Sasai et al., 2016 ), protein-DNA binding ( Munshi et al., 2018b ), quantifying folding pathways at different levels of resolution ( Henry et al., 2013 , Kubelka et al., 2008 , Gopi et al., 2017 ), force-spectroscopic measurements ( Imparato et al., 2007 ) and even crowding effects ( Caraglio and Pelizzola, 2012 ).
Fig.
…”
Section: Introductionmentioning
confidence: 99%
“…The Wako–Saitô–Muñoz–Eaton (WSME) model is promising for describing protein-folding reactions [ 17 ]. The WSME model is a coarse-grained model of proteins based on a simple and elementary statistical mechanical theory and can readily calculate free-energy landscapes using the 3D native structures of proteins [ 13 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%